Survey of local cannabidiol use in parents of children with epilepsy in Thailand: the prevalence, perceptions, and knowledge - Monsicha Ngampoopun; Charcrin Nabangchang; Piradee Suwanpakdee (BMC, 2022)
Abstract Background In 2019, Thailand legalized cannabidiol (CBD) for intractable epilepsy. The purpose of this study was to collect information regarding the experience and knowledge of CBD use in pediatric epilepsy. To the best of our knowledge, this is the first CBD survey in pediatric epilepsy in Southeast Asia. Method We performed a cross-sectional survey among all parents of pediatric epilepsy patients seen in the Pediatric Neurology Clinic at Phramongkutklao Hospital, Bangkok, Thailand between November 2018 and July 2020. The survey comprised 34 questions that assessed the demographics, knowledge, experiences, and opinions of parents/guardians regarding CBD use. The results were summarized using descriptive statistics. In addition, logistic regression was used to predict the factors for CBD use. Results Overall, 166 respondents (100%) participated in the study. Among the respondents, 9% have experienced using CBD; 56.25% of these reported reduced seizure frequency. CBD products were mostly obtained from folk healers (31.25%) and foreign products (25%). Common adverse effects included headache and nausea (31.5%). The number of anti-seizure medications (OR: 12.28, 95% CI: 1.27-118.8), knowledge of CBD as treatment for epilepsy (OR: 14.7, 95% CI: 1.43-150.87), and knowledge of CBD side effects (OR: 12.73, 95% CI: 2.77-58.43) were factors significantly associated with CBD use. Regarding CBD knowledge, our survey showed 80.72% of the respondents did not know the CBD compound for treating epilepsy, and 89.16% were not aware of CBD side effects. Interestingly, despite a lack of knowledge, 77.11% of the respondents expressed willingness to participate in future CBD trials. Conclusion Our survey highlights that half of the parents of patients who previously used CBD reported reduced seizure frequency; however, none became seizure-free. Additionally, there were gaps in knowledge regarding the use of CBD. These findings suggest that the implementation of cannabidiol knowledge is crucial for both public and healthcare professionals. Survey limitations due to the retrospective nature of the self-report could have resulted in recall bias.